Analisis Bibliometrik pada Database Dimensions dalam Penelitian Radikalisme Islam di Indonesia - Diana Artika; Busro Busro (UIN Sunan Gunung Djati Bandung, 2023)
Radicalism is a response to the conditions that are happening, the response is then manifested in the form of evaluation, rejection, and even violent resistance. The phenomenon that is common in Indonesia in terms of radicalism is related to religion. This research uses qualitative methods to identify research trends in the theme of Islamic Radicalism. As well as using bibliometric analysis by using the Dimensions database. There are five stages carried out in this study, namely keyword determination, data search, article selection, data validation, and data analysis. In writing a data analysis report on the key word taken, namely